Clinical effective use of Conquest Pro 12 Sharpened Tip for chronic total occlusion intervention: A series of three case reports. Issue 2 (16th February 2023) - Matsuda, Hiroaki; Tsuchikane, Etsuo; Yoshikawa, Ryohei; Okamura, Atsunori
Abstract: A new chronic total occlusion (CTO) guidewire, Conquest Pro 12 Sharpened Tip (CP12ST), has a stronger penetration force than the original CP12 and a deflection effect that it does not have. The CP12ST enables us to advance into hard plaque that has not ever penetrated, which might change CTO treatment as shown in three cases.